2021
DOI: 10.3389/fimmu.2020.620972
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expression of Endosomal Toll-Like Receptors—A Necessity or a Superfluous Duplication?

Abstract: Timely and precise delivery of the endosomal Toll-like receptors (TLRs) to the ligand recognition site is a critical event in mounting an effective antimicrobial immune response, however, the same TLRs should maintain the delicate balance of avoiding recognition of self-nucleic acids. Such sensing is widely known to start from endosomal compartments, but recently enough evidence has accumulated supporting the idea that TLR-mediated signaling pathways originating in the cell membrane may be engaged in various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 138 publications
(201 reference statements)
0
35
0
Order By: Relevance
“…For example, it has been reported that in cortical and hippocampal neurons where TLR7 is localised to the endosomes, stimulation with let‐7b, another TLR7 ligand, led to apoptosis (Lehmann et al., 2012), whereas in sensory neurons where TLR7 is localised to the plasma membrane, let‐7b binding led to stimulation of the cation channel transient receptor potential A1 (TRPA1) (Park et al., 2014). Similarly, TLR7 is expressed on both cell surface and endosomes in macrophages (Mielcarska et al., 2020), however it is exclusively present in endosomes in microglia (Kumar, 2019), therefore it is likely to see differences in ligand binding response between RAW 264.7 cells and WT‐MG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that in cortical and hippocampal neurons where TLR7 is localised to the endosomes, stimulation with let‐7b, another TLR7 ligand, led to apoptosis (Lehmann et al., 2012), whereas in sensory neurons where TLR7 is localised to the plasma membrane, let‐7b binding led to stimulation of the cation channel transient receptor potential A1 (TRPA1) (Park et al., 2014). Similarly, TLR7 is expressed on both cell surface and endosomes in macrophages (Mielcarska et al., 2020), however it is exclusively present in endosomes in microglia (Kumar, 2019), therefore it is likely to see differences in ligand binding response between RAW 264.7 cells and WT‐MG.…”
Section: Discussionmentioning
confidence: 99%
“…While it is well known that intracellular TLRs are physically separated from the cell surface to prevent autoimmune responses following receptor activation by host nucleic acids [74], interestingly, several studies have suggested the cell surface positioning of endosomal TLRs in certain cell types [75][76][77][78]. Cell surface expression of TLR3 was observed in human fibroblast cell lines [79], mouse splenic CD8 + dendritic cells, and marginal zone B cells [80].…”
Section: Intracellular Tlrsmentioning
confidence: 99%
“…These receptors enable multilayered protection and are located either externally on the surface membrane and/or internally in the cytosol and endosomes depending on the specific subtype (Fig. 1) (3,68,69) TLRs have been identified on multiple cell types, including endothelial and epithelial cells, and immune cells such as macrophages, monocytes, dendritic cells, neutrophils, and microglia. TLR expression is not only limited to immune cells but is also expressed on endothelial, epithelial cells, neuronal cells, neuronal progenitor cells, astrocytes, oligodendrocytes, satellite cells, myocytes, and platelets (Fig.…”
Section: Toll-like Receptor Signalingmentioning
confidence: 99%